Influência da privação de nitrogênio no cultivo da microalga Chlamydomonas reinhardtii visando a produção de lipídeos - Recalcatti, Jonas Felipe (2016)
The necessity of alternative energy sources is an example of action that may contribute to diminish environment related issues. Thus, biofuels rise as an option that fit to sustainable development, because they are produced from renewable sources of energy in order to reduce harmful gas emissions to the environment. Studies approach the potential of micro-algae to produce biodiesel, a biofuel obtained from the oil of oilseeds and micro-algae. The micro-algae consist of a variety of autotrophic, prokaryotic or eukaryotic organisms. Their simple structure allows them to easily convert solar energy into chemical energy. The products of this conversion are been used to obtain biomass from micro-algae and, consequently, products of commercial applications. Some micro-algae contain high levels of lipid, showing the potential of these microorganisms to produce biofuels. In this way, the objective of this paper was to study the micro-algae Chlamydomonas reinhardtii cultivation, growing with and without nitrogen, for the extraction and quantification of oil from this biomass in different temperatures and the analysis of the composition of the fatty acids produced. From the results obtained with the extraction, it has been seen that the deletion of nitrogen influence lipids productivity, rising the levels of the lipids on the micro-algae biomass when compared to lipids levels of the biomass cultivated with nitrogen, showing better outcomes when extracted at the temperature of 45º C (7% with nitrogen and 11% without nitrogen), independently of cultivation conditions. The deletion of nitrogen on the cultivation does not interfere significantly with the composition of the fatty acids in the oil of the biomass from the micro-algae. What predominates in its composition are saturated fatty acids (C 16:0) and mono-unsaturated (C 14:1, C 16:1 and C 20:1), propitious to biodiesel production. The results obtained show that the biomass Chlamydomonas reinhardtii micro-algae has the potential to produce biodiesel, when cultivated on the conditions tested on this paper.